Peningkatan Hasil Belajar Materi Pranata Sosial dalam Kehidupan Masyarakat Menggunakan Pembelajaran Kooperatif Tipe Stad Siswa - Ahmad Jais (CV. Syntax Corporation Indonesia, 2023)
The purpose of this study is to Improve Learning Outcomes of Social Institution Material in Community Life Using STAD Type Cooperative Learning for Class VIII Students of UPT SMP Negeri 6 Alla. The method used in this study is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. Based on the results of action research that STAD Type Cooperative Learning can Improve Learning Outcomes of Social Institution Material in Community Life of Class VIII Students of UPT SMP Negeri 6 Alla.. Furthermore, the researchers recommend: (1) For teachers who have the same difficulties can apply STAD Type Cooperative Learning to improve Learning Outcomes. (2) In order to get maximum results, teachers are expected to make STAD Type Cooperative Learning more interesting and varied.